High dynamic range, low power, tunable, active filter for RF and microwave wireless applications. Issue 4 (14th February 2018) - Pantoli, Leonardo; Stornelli, Vincenzo; Leuzzi, Giorgio
Abstract : In this work, a novel solution for the design of active filters is presented. The proposed approach is based on the use of single‐transistor active inductors in class‐AB operation with minimum power consumption (2 mW) and good dynamic range (about 100 dB). This approach also allows potential implementation of monolithic technology. The proposed solution has been validated with a hybrid prototype, fabricated and tested in the authors' labs. The measured performances demonstrate its feasibility for use in commercial applications.